Improving Student Learning Outcomes Through Innovative Textbooks In Writing Persuasive Texts - Fatmawati, Yeni; Purnomo, Mulyadi Eko; Suhendi, Didi (Jurnal Pendidikan Indonesia, 2022)
The ability to write persuasive texts is a skill that is not easy to master. The low level of students' understanding and memory of the material taught orally and in writing. In addition, the lack of learning resources is also an obstacle for students in learning. This study aims to develop a persuasive text writing book and analyze the potential effects of a persuasive text writing book. This research method uses the Jolly and Bolitho and Tesmer development model. This research is research and development research. Methods This research adapts the Jolly and Bolitho development and Tessmer development models. Data collection techniques used three techniques, questionnaire techniques, interviews, and tests. The data collection instrument is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis quantitative and inferential statistics. The study results, the expert validation assessment, obtained very good results from content, language, presentation, and graphics feasibility. The field test results through the paired simple test showed a significant difference between the scores before and after using this developed textbook. It was concluded that writing persuasive textbooks could make it easier for students to understand writing to improve student learning outcomes.